Nipa Fruit Flour (Nypa fruticans) Potential as a Prebiotic on Lactobacillus plantarum sp - Ahmad Mustangin (Journal of Innovative Food Technology and Agricultural Product, 2026)
Nipa plants (Nypa fruticans (Thunb.) Wurmb) are found in West Kalimantan and have not been utilized optimally. Nipa fruit flour contains high carbohydrates, it could be potential as a prebiotic source. This research aims to determine the proximate characteristics and prebiotic activity of nipa flour in Lactic Acid Bacteria in vitro. Prebiotic activity of nipa fruit flour was determined by calculating changes in probiotic cell biomass growth after being incubated for 24 dan 48 hours in 2% nipa fruit flour or 2% glucose then compared with changes in enteric cell biomass growth. The bacteria used are Lactobacillus plantarum, Lactobacillus acidophilus, Bifidobacterium longum as probiotics and Escherichia coli as enteric. The results showed that nipa fruit flour has a moisture content of 10.51%, ash of 1.70% , fat of 1.39%, protein of 1.64%, crude fiber of 38.90%, carbohydrate of 45.86%, yield of 55.41% and tan color of flour. Prebiotic activity of nipa fruit flour showed positive activity to L. plantarum 2.274 after 24 hours and 0.365 after 48 hours incubation and negative prebiotic activity to L. acidophilus (-0.158) after 48 hours incubation and B. longum (-0.532) after 24 hours incubation. The conclusion of the research is that nipa fruit flour has the potential as a prebiotic source with probiotics Lactobacillus plantarum. keywords: flour, nipa fruit, prebiotic activity